INDONESIA-CHINA’S BILATERAL TRADE PATTERN ANALYSIS, PRE AND POST FULL IMPLEMENTATION OF THE ACFTA - Aditya P. Alhayat (Widyariset, 2012)
This paper intends to study whether Indonesian-China’s bilateral trade pattern has substantially changedafter the full implementation of ASEAN-Cina Free Trade Agreement (ACFTA) in 2010. It also identifies the tradesectors which have comparative advantage and comparative disadvantage with China. Utilizing descriptivequantitative analysis, this study comparing the trade patterns pre and post ACFTA. The results showed that thetrade patterns between the two countries are relatively similar between before and after ACFTA. In addition, manyIndonesia’s commodity exports are still based on natural resources. Therefore, it needs trade policies to encouragehigher value-added of the products.